PERSEPSI WIRAUSAHA SEBAGAI PILIHAN KARIER PADA SISWA DI SMK ABDURRAB PEKANBARU - Wahyuningsih, Endah (Komunitas Manajemen Kompetitif, 2025)
This study was conducted at SMK Abdurrab located on Jalan Delima, Tobekgodang Village, Binawidya District, Pekanbaru City, with the aim of determining the perception of class XI students of SMK Abdurrab towards entrepreneurship as a career choice. Do students understand the concept of entrepreneurship as a promising career? Do students understand the risks of entrepreneurship as a career and do students feel confident in starting a business if given support and guidance. The population of this study was class XI students of SMK Abdurrab Pekanbaru in the 2024/2025 academic year totaling 184 people. Sampling was carried out using proportional random sampling technique of 87 people. Quantitative data were analyzed using descriptive and percentage. Data were collected using a questionnaire using the Licert scale. Based on the results of the study, it can be concluded that the majority of SMK Abdurrab Pekanbaru students have a positive perception of entrepreneurship as a career choice. They understand the concept, are interested in running it, and see it as a promising career. Despite concerns about the risks, students feel confident in starting a business if given support and guidance. Schools also play an important role in fostering an entrepreneurial spirit in class XI students of SMK Abdurrab Pekanbaru